ANALISIS CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Efriyenti, Dian (Aksara Public, 2018)
In a modern era like now there are still Indonesian companies that have seen CSR as beyond compliance, including PT. Djarum, PT. Unilever (Lifeboy, Pepsodent, etc.), PT. Danone (Aqua). One of the reasons CSR is needed for companies is to facilitate the company's goals, namely in obtaining good goodwill. Recently there has been a tendency (trend) to increase public demands for transparency and accountability of the company as a manifestation of the implementation of good corporate governance (GCG). The size of a company will certainly show how strong the company's concern for the environment and the company's transparency in its performance. The research sample is a manufacturing company listed on the Indonesia Stock Exchange, with 13 food and beverage sub-sector companies. The results of the study state that partially CSR, managerial ownership, institutional ownership affect the value of the company. While independent commissioners do not affect the value of the company. The size of the company influences the relationship between managerial ownership, institutional ownership and independent commissioners on the value of the company. While company size does not moderate the relationship of CSR to company value.